Pengaruh Pemberian Ekstrak Jahe Merah (Zingiber officinale var. rubrum) terhadap Intensitas Nyeri Dismenore pada Remaja Putri di Desa Kanigoro, Dusun Krajan, Kecamatan Pagelaran, Kabupaten Malang - Risma Andreani; Raden Maria Veronika Widiatrilupi (Journal of Innovative and Creativity, 2025)
Dysmenorrhea is a common menstrual pain complaint experienced by adolescent girls, which can disrupt daily activities and reduce overall quality of life. One increasingly studied alternative for menstrual pain management is the use of herbal remedies, including red ginger (Zingiber officinale var. rubrum), known for its natural anti-inflammatory and analgesic properties. This study aims to evaluate the effect of red ginger extract on the intensity of dysmenorrhea among adolescent girls in Kanigoro Village, Pagelaran District, Malang Regency. Using a quasi-experimental method with a one-group pre-test post-test design, 30 participants received an oral intervention of red ginger extract. The Wilcoxon Signed Ranks Test showed a statistically significant difference in pain intensity before and after the intervention (p = 0.000), with pain levels decreasing from moderate and severe categories to mild or no pain. These findings suggest that red ginger extract is effective in alleviating menstrual pain and holds potential as a natural solution that can be widely applied within communities that embrace herbal-based traditions.